Newly diagnosed diabetes has high risk for cardiovascular outcome in ischemic stroke patients - Kyung-Hee Cho (Nature Portfolio, 2021)
Abstract We investigated cardiovascular outcomes in ischemic stroke patients with newly diagnosed diabetes mellitus (DM) compared with those of patients with previously known DM and no DM using the glycosylated hemoglobin (HbA1c) criteria. The relationship between new DM diagnosis and cardiovascular risk remains unclear to date. We performed post hoc analysis using the data of participants from the Prevention of Cardiovascular events in iSchemic Stroke patients with high risk of cerebral hemOrrhage (PICASSO) trial. Newly diagnosed DM was defined as HbA1c of ≥ 6.5% without known DM history. The outcome was the incidence of composite cardiovascular events, including stroke (ischemic and hemorrhagic), myocardial infarction, and cardiovascular death. In total, 1306 patients were included; 38 patients (2.9%) had newly diagnosed DM; 438 patients (33.5%), known DM; and 830 patients (63.6%), no DM. In patients with newly diagnosed DM, known DM, and no DM, the incidence of ischemic stroke was 8.93, 3.79, and 2.64 per 100 person-years (log-rank test; p = 0.0092), while that of composite cardiovascular events was 8.93, 5.92, and 3.87 per 100 person-years (p = 0.025), respectively. Newly diagnosed DM was an important risk factor for ischemic stroke and composite cardiovascular events after ischemic stroke. Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT01013532.